Parasite excretory‐secretory products and their effects on metabolic syndrome. (26th March 2017) - Crowe, J.; Lumb, F. E.; Harnett, M. M.; Harnett, W.
Summary: Obesity, one of the main causes of metabolic syndrome (MetS), is an increasingly common health and economic problem worldwide, and one of the major risk factors for developing type 2 diabetes and cardiovascular disease. Chronic, low‐grade inflammation is associated with MetS and obesity. A dominant type 2/anti‐inflammatory response is required for metabolic homoeostasis within adipose tissue: during obesity, this response is replaced by infiltrating, inflammatory macrophages and T cells. Helminths and certain protozoan parasites are able to manipulate the host immune response towards a TH2 immune phenotype that is beneficial for their survival, and there is emerging data that there is an inverse correlation between the incidence of MetS and helminth infections, suggesting that, as with autoimmune and allergic diseases, helminths may play a protective role against MetS disease. Within this review, we will focus primarily on the excretory‐secretory products that the parasites produce to modulate the immune system and discuss their potential use as therapeutics against MetS and its associated pathologies.